Synthesis and Characterization Zinc Oxide Nanoparticles Using Plant Extra - Hadi, Abdullah Talib; al-Mohaymin Mohammad, Mohammad Abd; Jaburi, Duha Basheer; Mahmud, Muthanna (Journal of Science in Medicine and Life, 2024)
This study used orange leaf extract with zinc chloride as precursor to success fully create zinc oxide nonparties (ZnO). Were synthesized and characterized by various techniques such as x-ray diffraction(XRD),and field emission scanning electron microscopy (FE-SEM).XRD confirmed the crystalline nature for (ZnO)nano particles with a crystal size calculated using the Debye-Scherer equation estimated to be183.79 nm-FE-SEM image showed that the ZnO have spherical-shape.